2019
DOI: 10.1080/09654313.2019.1609425
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the normative turn in regional innovation policy: responsibility and the quest for public value

Abstract: The perceived ineffectiveness of traditional innovation policies in solving societal challenges such as poverty, ageing, climate change as well as problems of regional economic restructuring has motivated a recent 'normative turn' in innovation policy. This has shifted the debate on the rationales for intervention from market and system failures to accommodate more transformative views but also other approaches rooted in the notion of public value and has led innovation scholars to question not just the how an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 56 publications
0
42
0
12
Order By: Relevance
“…von Schomberg (2008) uses the term collective responsibility to frame this concept, which is a broader understanding of the actors responsible for ensuring the positive impacts of research and innovation. This feature suggests that RRI should incorporate issues of directionality and normativity, including societal values fostered by research and innovation (Uyarra et al, 2019). A general fear is that research policy is too heavily oriented towards excellence, while innovation policy is focused exclusively on competitiveness.…”
Section: Rrithe Development Of a Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…von Schomberg (2008) uses the term collective responsibility to frame this concept, which is a broader understanding of the actors responsible for ensuring the positive impacts of research and innovation. This feature suggests that RRI should incorporate issues of directionality and normativity, including societal values fostered by research and innovation (Uyarra et al, 2019). A general fear is that research policy is too heavily oriented towards excellence, while innovation policy is focused exclusively on competitiveness.…”
Section: Rrithe Development Of a Frameworkmentioning
confidence: 99%
“…Relatedly, the recent RRI literature contributes insight into research and innovation stewardship, including how these can become more inclusive and sustainable. RRI offers forward-looking approaches and frameworks for reflecting on societal impacts, with a focus on participatory research and innovation methods (Owen, Macnaghten, & Stilgoe, 2012;Uyarra, Ribeiro, & Dale-Clough, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the empirical investigation shows that green transformations can be governed quite directly through such public procurement. Thus, more than public procurement having a direct environmental effect in that it reduces emissions, the investigation has also shown that it is good innovation policy (Uyarra et al, 2019). The lesson from Ampere shows, for example, that setting 'technology neutral' demands will allow for industries to come up with the best solutions to societal problems (e.g.…”
Section: Multi-actor Institutional Agency -mentioning
confidence: 99%
“…In relation to this, in a forthcoming article (Dale-Clough et al, 2019) we argue that more attention should be given to the role of demand in the creation of public value and achieving transformative change in regions, understood not just as diversifying an economy's industrial structure but also as transforming it in socially desirable directions. Smart specialisation lacks a normative focus, being more concerned with the economic competitiveness of places.…”
Section: Demand Side Innovation Policymentioning
confidence: 99%